Relation between insomnia and stress, anxiety, and depression among Egyptian medical students. Issue 3 (July 2016) - Barakat, Doaa; Elwasify, Mohamed; Elwasify, Mahmoud; Radwan, Doaa
Abstract : Background: There has been a growing attention paid to depression, anxiety, and stress among college students. Only few studies have assessed these topics among medical students, and fewer still have been conducted in Arab countries. Furthermore, the relation of depression, anxiety, and stress to insomnia has not been thoroughly investigated. Participants and methods: This cross-sectional, questionnaire-based observational study explored the prevalence of stress, anxiety, and depression and their relationship to insomnia among 980 undergraduate medical students of Mansoura University. The data were gathered using a demographic questionnaire, the Insomnia Severity Index, and the Depression Anxiety Stress Scale. Results: The prevalence of symptoms of stress, anxiety, and depression was 63.7, 66.9, and 59.2%, respectively. There were significant associations with multiple demographic variables. There was a significant positive correlation between Insomnia Severity Index score and stress, anxiety, and depression scores. Different stressors were identified by the students, including residence, working while being educated, studying more than 4 h a day, difficulty studying in English, problems communicating with the teaching staff, fear of failure in the future, death of a family member, chronic illness of a family member, physical health problems, and problems due to coping with academic demands. Conclusion: Stress, anxiety, and depression are common among medical students in Egypt, and are correlated with insomnia.